Uncertainties in long-term wave modelling. (July 2022) - Bitner-Gregersen, Elzbieta M.; Waseda, Takuji; Parunov, Josko; Yim, Solomon; Hirdaris, Spyros; Ma, Ning; Guedes Soares, C.
Abstract: Uncertainties of wave data and models got increasing attention in the last decades by the marine industry because of their importance for safety at sea. Improved knowledge about wave description and related uncertainties leads to a reduction of safety factors, and consequently building costs of marine structures. The ISSC (International Ship and Offshore Structures Congress) and ITTC (International Towing Tank Conference) organizations have also been concerned with uncertainties associated with wave data and models used for the design and laboratory testing of marine structures. The different emphasis on uncertainty modelling by these organizations led to a somewhat different approach or at least different nomenclature adopted for uncertainty modelling. This study highlights these differences, but also existing similarities, in the context of ocean waves. It is addressing long-term wave description; the wave data and the models used to extrapolate to extreme values. The investigations point out different sources of uncertainties in existing wave data sets and models which may impact design and operations of ships and offshore platforms and should get attention. The presented results are applicable to all types of marine structures. Highlights: Wave Group of ISSC-ITTC 2018 Committee on Uncertainty Modeling. Uncertainty classification used by the ISSC and ITTC organizations. Uncertainties assocaited with wave data and long-term wave models.